Legal Consciousness and Living Legal Reasoning: Penghulus and Mediation in Resolving Marital Disputes at the Religious Affairs Office of East Pontianak - Kamaliah, Mukarramah; Yazid, Mhd (Indonesian Journal of Sharia and Socio-Legal Studies, 2025)
The increasing reliance on non-litigation mechanisms to resolve marital disputes, particularly mediation at the Religious Affairs Office (KUA), reflects a significant shift in contemporary practice in Islamic family law in Indonesia. Within this institutional setting, penghulus serve simultaneously as state officials and religious authorities who interpret and apply legal norms within dynamic social contexts. This article provides a socio-legal analysis of mediation practices at the KUA of East Pontianak, with particular attention to the legal reasoning employed by penghulus in addressing marital conflicts. Drawing on qualitative methods, including in-depth interviews and institutional document analysis, the study finds that marital disputes typically arise from complex interactions involving fragile communication, gendered role asymmetries, and economic pressures—factors that significantly shape mediation dynamics. The mediation process unfolds through systematic yet flexible stages (pre-mediation, core mediation, and post-mediation), enabling penghulus to tailor their strategies to the emotional, social, and moral circumstances of the disputing parties. The findings demonstrate that penghulus employ an integrative form of legal reasoning that synthesizes Islamic legal norms, state law, local cultural values, and psychosocial considerations to construct persuasive arguments and facilitate reconciliation. This article argues that these practices constitute a form of living legal reasoning that reflects the mediators’ legal consciousness, wherein multiple legal and social norms are renegotiated to produce mutually agreed, restorative, and welfare-oriented outcomes. [Meningkatnya penggunaan mekanisme non-litigasi dalam penyelesaian sengketa perkawinan, khususnya mediasi di Kantor Urusan Agama (KUA), mencerminkan pergeseran penting dalam praktik hukum keluarga Islam kontemporer di Indonesia. Dalam konteks kelembagaan tersebut, para penghulu berperan ganda sebagai aktor negara sekaligus otoritas keagamaan yang menafsirkan dan menerapkan norma hukum dalam situasi sosial yang dinamis. Artikel ini menyajikan analisis sosio-legal terhadap praktik mediasi di KUA Kecamatan Pontianak Timur, dengan fokus pada bentuk penalaran hukum yang digunakan oleh para penghulu ketika menangani sengketa rumah tangga. Dengan menggunakan metode kualitatif melalui wawancara mendalam dan analisis dokumen kelembagaan, penelitian ini menemukan bahwa sengketa perkawinan umumnya muncul dari interaksi berlapis antara kerentanan komunikasi, ketidakseimbangan peran gender, dan tekanan ekonomi, sejumlah faktor yang membentuk dinamika mediasi secara signifikan. Proses mediasi berlangsung melalui tahapan pra-mediasi, inti mediasi, dan pasca-mediasi yang sistematis namun fleksibel, sehingga memungkinkan para penghulu menyesuaikan strategi dengan kondisi emosional, sosial, dan moral para pihak yang berselisih. Selain itu, temuan penelitian juga menunjukkan bahwa para penghulu menerapkan model penalaran hukum integratif yang menggabungkan norma hukum Islam, hukum negara, nilai budaya lokal, serta pertimbangan psikososial untuk membangun argumentasi hukum dan memfasilitasi rekonsiliasi. Artikel ini berargumen bahwa praktik mediasi tersebut merupakan bentuk penalaran hukum hidup yang mencerminkan kesadaran hukum para mediator, di mana beragam norma hukum dan sosial dinegosiasikan kembali untuk menghasilkan kesepakatan yang restoratif, disepakati bersama, dan berorientasi pada kemaslahatan.]